Informational Support of Civilian Intelligence for Heavy Industry (Including Machine Industry) and the Energy Sector in the Polish People’s Republic in the Years 1970–1990 - Sikora, Mirosław (Studia Historiae Oeconomicae, 2018)
Throughout the existence of the Polish People’s Republic (PPR), its scientific and technical intelligence (S&TI) supported Polish mining, energy, metallurgy, and machine industries. Cooperation with companies and research and development centers intensified in the first half of the 1970s, as a natural consequence of the experience accumulated by the intelligence service in the previous fifteen years. The most crucial issues related to the improvement of secret methods of acquiring technologies for the Polish economy were defining the scope of the tasks, i.e. the types of technologies which can be acquired by intelligence or purchased in the black market, selecting objects, (i.e. institutions and organizations with the required knowledge), and recruiting personal sources of information in western facilities. Apart from acquiring specific solutions S&TI also developed analyses related to specific countries, as well as to specific technologies in the global aspect or to international corporations that possessed the technologies. Furthermore, S&TI was engaged by the Polish government to provide information to the Ministry of Foreign Affairs and the Ministry of International Trade during trade negotiations with foreign contractors. Author draws the history of Polish S&TI during the 70s and 80s, showcasing its operations, explaining its modus operandi and discussing the question about the efficiency of illicit transfer of know-how from OECD for the purposes technical progress in communist Poland. Article bases on recently declassified documents of Polish intelligence service from the pre-1990 period. There are moreover other archival records as well as secondary sources explored.